MENTORING, AN ALTERNATIVE EFFORT TO DEVELOP GOVERNMENT EMPLOYEES’ COMPETENCIES - Mila Rosmaya (Polteknik Imigrasi, 2018)
A change is something obsolute and mandatory. People also do change. In the context of a public service the people are categoried into demanders and suppliers (providers). Needs of the demander keep changing. The changes happen to variant, quantity of the people’s needs as well as process of how they expect to get their needs. To keep up with these changes and, moreover, to improve the quality of the public service they supply to the demanders, the providers need to make some changes. The change that should take at the first place is their competency. They should get competency development provided by an orgnization where they belong to. Among many available alternatives of the competency development methods, mentoring is something else. It involves the right person who shares expertise and trains the competency needed by a trainee (mentee) because the person is the mentee’s supervisor who can directly monitor and evaluate the progress of the mentoring. This method generates benefits not only for the individuals involved but also the organization. For the organization the mentoring is both efficient and effective. It costs almost zero budget. Despite the obstacles that may occur the mentoring is a bull’s eye.